ICOs conceptual unveiled: scholarly review of an entrepreneurial finance innovation - Mayank Joshipura; Rim El Khoury; Muneer M. Alshater (Financial Innovation)
Abstract This review synthesizes 48 academic studies on Initial Coin Offerings (ICOs) from 2018 to 2023, employing bibliometric and content analyses to illuminate their complexities and innovation in entrepreneurial finance. It identifies four key themes: (1) regulatory intricacies, market transformation, and strategic implications for emerging ventures; (2) the opportunities and challenges presented, and key factors influencing the success of ICOs; (3) ICOs and entrepreneurial finance; and finally, (4) review of reviews. By examining the intersection of legal frameworks, disruptive potential, and stakeholder challenges, this interdisciplinary perspective captures the essence of ICOs and charts a course for future inquiry. It serves as a pivotal reference for researchers, practitioners, and regulators to understand the multifaceted ICO landscape and its implications for the future of finance.